CONSIDERATIONS REGARDING THE ENERGY CRISIS STARTED IN 2021 - Luiza Mădălina APOSTOL (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
The paper "Considerations Regarding the Energy Crisis Started in 2021" presents the main causes and consequences of the current energy crisis, as well as a series of measures established by the European Commission, aiming at maintaining the stability on the European natural gas markets, ensuring Europe's independence from the fossil fuels of Russia well before 2030, accelerating the transition to green energy, while increasing the resilience of the EU's energy system.